Correlation Analysis of Earthquake Intensity Measures and Engineering Demand Parameters of Reactor Containment Structure - Vu, X. H.; Nguyen, T. T. T.; Phan, V. L.; Nguyen, D. D. (Engineering, Technology & Applied Science Research, 2022)
This study aims to analyze the correlation between earthquake Intensity Measures (IMs) and seismic responses of a reactor containment building in an APR-1400 nuclear power plant. A total of 20 IMs were employed to develop Seismic Demand Regression Models (SDRMs), which show the relationship between IMs and engineering demand parameters. A numerical model of the structure was constructed using the Lumped-Mass Stick Model (LMSM) in SAP2000. Additionally, a three-dimensional finite element model was developed to validate the simplified LMSM approach. A set of 90 ground motion records was used to perform a time-history analysis, where the motions cover a wide range of amplitude, intensity, epicenter distance, significant duration, and frequency of earthquakes. Engineering demand parameters were monitored in terms of floor accelerations and displacements. Consequently, strongly correlated IMs were identified based on the evaluation of SDRMs using four statistical indicators: coefficient of determination, standard deviation, practicality, and proficiency. The results showed that the strongest IMs were Sa(T1), Sv(T1), and Sd(T1) followed by ASI, EPA, PGA, and A95. On the other hand, the weakly correlated IMs were PGD, DRMS, SED, VRMS, PGV, HI, VSI, and SMV.